A Multivariable Twin-Rotor System Control Design - Pathan, E.; Khan, M. H.; Aslam, M. K.; Asad, M.; Arshad, H.; Rabani, M. I. (Engineering, Technology & Applied Science Research, 2021)
This paper presents the design of a Multi-Input Multi-Output (MIMO) PID controller for a twin-rotor MIMO system. A multivariable control system consisting of two loops is designed for a non-linear system with two inputs and two outputs. The designed controllers have been tested on a simulated model with different possibilities and real-time results were taken. The designed PID controller efficiently controls the loops of the system and does not suffer from any process interactions. The results indicate that the performance of the PID controllers is excellent and both the transient and the steady-state enactment are adequate. The yaw and pitch rotor’s real-time responses are almost the same as the desired ones.